Proses Batambua Sampai Ama Pada Pesta Pernikahan di Kenagarian Tanjung Sani, Maninjau. - Muhammad Hadi, Fitriah Azizah; Syeilendra (Universitas Negeri Padang, 2024)
The aim of this research is to explain the process of batambua until ama at a wedding party in Kenagarian Tanjung Sani. The research method used is qualitative research using a descriptive analytical approach. Data collection techniques were carried out by conducting literature studies, field observations, interviews and documentation. Then analyze the data by collecting data, simplifying, grouping and drawing conclusions. This research shows that the process of batambua to ama at a wedding party is held in two different styles, namely at Alek Pemuda where the tambua players immediately form an arena formation in the courtyard of the event house and at Alek Bako or Alek Saduduak where the tambua players do the procession first and then continue. by forming an arena formation. The song sung was Atam Sikapak with the division of Atam Marakpulai Katurun, Atam Hoyak and Atam. Meanwhile, for the song content, namely Hujan Labek, Cancang Rabuang, Kureta Api Mandaki and Randang Kacang, the Atam Hoyak song will continue to be repeated until it reaches a fast tempo (allegro) and with loud dynamics (forte). The playing of the Atam Hoyak song triggers an emotional reaction in the player. tambua until ama it reaches the same condition.